Self-Esteem Ditinjau Dari Dukungan Keluarga dan Jenis Kelamin Pada Siswa MA Hamzanwadi NWDI Pancor - Nurholik Azizah; Hasaniah Zulfiani; Husnawati Husnawati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
The aim of this research is to describe and explain the relationship between family support and student self-esteem and describe the level of differences in self-esteem of male and female students at MA Hamzanwadi NWDI Pancor. This research uses a quantitative approach using correlational and comparative methods. The measuring instrument in this research uses two scales, namely the self-esteem scale and the family support scale. The total research sample was 92 students, 46 male students and 46 female students. The research was conducted at MA Hamzanwadi NWDI Pancor, East Lombok. Sampling was carried out using the purposive sampling method. The results of the research show that the significance value of the self-esteem variable and the family support variable is p = 0.00 < 0.05, so the variables are said to be correlated. The level of correlation between variables is 0.644 or around 64.4% of students' self-esteem is influenced by family support. Meanwhile, the description of the level of self-esteem of male and female students obtained a sig value. 0.865 > 0.05, so the average self-esteem score for male and female students is the same.